2015
DOI: 10.5812/aapm.31111
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Out-of-Plane vs. In-Plane Interscalene Catheters: A Randomized, Prospective Study

Abstract: Background:Continuous interscalene blocks provide excellent analgesia after shoulder surgery. Although the safety of the ultrasound-guided in-plane approach has been touted, technical and patient factors can limit this approach. We developed a caudad-to-cephalad out-of-plane approach and hypothesized that it would decrease pain ratings due to better catheter alignment with the brachial plexus compared to the in-plane technique in a randomized, controlled study.Objectives:To compare an out-of-plane interscalene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…In addition, patient randomization was not entirely random as there were financial difficulties for some patients to acquire elastomeric pump and this resulted in non-homogeneous groups in relation to age and size of each group. According to the study by Schwenk et al, 7 with the insertion of the needle into the plane it is possible to observe the dispersion of the anesthetic injected during the execution of the blockade and the insertion of the catheter at the desired site during US-IBPB, however the final position of the catheter might not be in the ideal location since the three-dimensional view of the catheters is unreliable. Finally, our sample did not detected rare complications of catheter insertion, like entrapment in the brachial plexus, insertion into the vertebral artery or epidural space with permanent loss of cervical spinal function and subarachnoid anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patient randomization was not entirely random as there were financial difficulties for some patients to acquire elastomeric pump and this resulted in non-homogeneous groups in relation to age and size of each group. According to the study by Schwenk et al, 7 with the insertion of the needle into the plane it is possible to observe the dispersion of the anesthetic injected during the execution of the blockade and the insertion of the catheter at the desired site during US-IBPB, however the final position of the catheter might not be in the ideal location since the three-dimensional view of the catheters is unreliable. Finally, our sample did not detected rare complications of catheter insertion, like entrapment in the brachial plexus, insertion into the vertebral artery or epidural space with permanent loss of cervical spinal function and subarachnoid anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation took into consideration previous studies witch found that the incidence of postoperative pain was 30% after shoulder arthroscopy 6 and that association of US-IBPB decreased the frequency of postoperative pain in patients who received US-IBPB anesthesia to 7.5% 7 being the risk difference, therefore, −0.22 with the 95% confidence interval from −0.30 to −0.075. Based on such evidences, the following parameters were used to consider the sample size calculation via G*power program 8 under a z -test family (two-tailed): Alpha error probability = 0.05, Power (1−beta error probability) = 0.80, Allocation ratio = 1.…”
Section: Methodsmentioning
confidence: 99%
“… 84 Different procedures of continuous interscalene technique (out-of-plane vs in-plane technique) can offer equivalent analgesia as concerning PACU pain ratings, and out-of-plane technique can be an alternative method when in-plane approach is difficult to be performed on some patients. 85 Ultrasound-guided interscalene nerve blocks for perioperative analgesia can be safely and effectively performed in obese patients with body mass index being associated with an increased peak PACU pain, PACU opioid administration, and incidence of PACU nausea. 86 …”
Section: Regional Anesthesia Techniquesmentioning
confidence: 99%
“…The out-of-plane technique can be principally used in situations where the in-plane technique is challenging or the needle direction is not clear. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to view the needle tip and confirm the needle advancement with tissue movement using the US image. [ 13 , 14 ] Needle advancement or LA injections without adequate needle tip visualization can cause unintentional vascular, neural, or visceral injuries. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%